Determining the prevalence of peri-implantitis in patients one year after prosthetic loading in Khorramabad in 2021 - Saman Nasiri; Faezeh Rafiei; Samad Darabian (Tehran University of Medical Sciences, 2021)
Background and Aims: Although dental implants have become a successful and predictable ong-term treatment for patients, not all implant treatments are necessarily successful and pre-implant diseases are spreading. The aim of this study was to determine the prevalence of peri-implantitis in patients one year after prosthetic loading in Khorramabad in 2021. Materials and Methods: In this cross-sectional study, 53 patients who had implants and undergone prosthetic loading for one year were studied. In each of the 53 patients, the probing depth (PD) and bleeding during probing (BOP) around the implant and the characteristics of the surrounding soft tissue, including gingival redness and tissue sensitivity were evaluated and recorded. To assess the bone level or possible bone resorption, a P.A. graph was taken from the patient using a parallel technique. Information such as demographic characteristics and specialized information about the disease were collected through a checklist. Data were collected using SPSS22 software. Frequency tables and chi-square and t-tests were used to analyze the data. Results: The mean age of patients participating in the present study was 46.5±10.63 years. The number of women was 33 (62.3%). The prevalence of peri-implantitis was 17% at the patient level and 9.3% at the implant unit level. There was a significant relationship between the age (P<0.03) and systemic disease (P<0.03) with the prevalence of peri-implantitis. However, there was no statistically significant relationship between the prevalence of peri-implantitis and other demographic variables (P<0.05). Conclusion: The results of the present study showed that the prevalence of peri-implantitis was higher in people with a higher mean age. In addition, systemic diseases are a protective factor for peri-implantitis.